Genomics of a phototrophic nitrite oxidizer: insights into the evolution of photosynthesis and nitrification - Hemp, James (ISME J, 2016)
Oxygenic photosynthesis evolved from anoxygenic ancestors before the rise of oxygen ~2.32 billion years ago; however, little is known about this transition. A high redox potential reaction center is a prerequisite for the evolution of the water-oxidizing complex of photosystem II. Therefore, it is likely that high-potential phototrophy originally evolved to oxidize alternative electron donors that utilized simpler redox chemistry, such as nitrite or Mn. To determine whether nitrite could have had a role in the transition to high-potential phototrophy, we sequenced and analyzed the genome of Thiocapsa KS1, a Gammaproteobacteria capable of anoxygenic phototrophic nitrite oxidation. The genome revealed a high metabolic flexibility, which likely allows Thiocapsa KS1 to colonize a great variety of habitats and to persist under fluctuating environmental conditions. We demonstrate that Thiocapsa KS1 does not utilize a high-potential reaction center for phototrophic nitrite oxidation, which suggests that this type of phototrophic nitrite oxidation did not drive the evolution of high-potential phototrophy. In addition, phylogenetic and biochemical analyses of the nitrite oxidoreductase (NXR) from Thiocapsa KS1 illuminate a complex evolutionary history of nitrite oxidation. Our results indicate that the NXR in Thiocapsa originates from a different nitrate reductase clade than the NXRs in chemolithotrophic nitrite oxidizers, suggesting that multiple evolutionary trajectories led to modern nitrite-oxidizing bacteria.